PENERAPAN MODEL CITIZEN UNTUK MENGUATKAN CIVIC DISPOSITION SISWA KELAS VB SD NEGERI BANJARANYAR 04 KECAMATAN BREBES - Leni Yunitasari; Azamul Fadhly Noor Muhammad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the need to strengthen the civic disposition of elementary school students, such as responsibility, discipline, cooperation, caring, tolerance, and democratic attitudes in school life. The purpose of this study is to describe the application of the Project Citizen model in strengthening the civic disposition of grade 6 students at Banjaranyar 04 Public Elementary School. This study used a descriptive qualitative approach, with grade 6 students and their class teachers as subjects. Data collection techniques were conducted through observation, interviews, and documentation. The results showed that the implementation of the Project Citizen model encouraged students to be more active in identifying problems in their surroundings, discussing, working together in groups, developing alternative solutions, and presenting project results responsibly. Through these learning stages, students' civic disposition values ​​were strengthened, particularly in the aspects of responsibility, social concern, cooperation, tolerance, and courage to express opinions. Thus, the Project Citizen model can be an effective alternative learning model for Pancasila Education to shape the civic character of elementary school students.